2022
DOI: 10.2340/jrm.v54.1407
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Potential Effects of Robot-Assisted Passive Range of Motion Training in Combination with Conventional Rehabilitation on Hand Function in Patients with Chronic Stroke

Abstract: Objective: To assess the effects of exoskeleton robot-assisted passive range of motion for induction training in combination with conventional hand rehabilitation in patients with chronic stroke.Design: Single-cohort.Subjects: Chronic stroke with severe upper extremity hemiparesis.Methods: Thirty sessions of therapy over a period of 10 weeks. Each session started with 30 min robot-assisted passive range of motion for the hand, followed by 30 min conventional hand rehabilitation. The Fugl-Meyer Assessment for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…AROM against gravity is theoretically a rapid indication of the ability of the spared motor system to activate the spinal motoneuron pools that move a particular segment in stroke survivors [33]. One study by Hsu et al reported the use of exoskeletal robotassisted PROM of the hand can be employed as an induction therapy for the stroke rehabilitation program [34].…”
Section: Discussionmentioning
confidence: 99%
“…AROM against gravity is theoretically a rapid indication of the ability of the spared motor system to activate the spinal motoneuron pools that move a particular segment in stroke survivors [33]. One study by Hsu et al reported the use of exoskeletal robotassisted PROM of the hand can be employed as an induction therapy for the stroke rehabilitation program [34].…”
Section: Discussionmentioning
confidence: 99%